Source Apportionment of Urban Ammonia and its Contribution to Secondary Particle Formation in a Mid-size European City - Laura Ehrnsperger; Otto Klemm (Aerosol and Air Quality Research)
Abstract Ambient air pollution caused by fine particulate matter (PM) and trace gases is a pressing topic as it affects the vast majority of the world’s population, with a particularly heavy influence in densely populated urban environments. Alongside nitrogen oxides (NOx) and PM, ammonia (NH3) is also a relevant air pollutant due to its role as a precursor of particulate ammonium. This is a study about the short-term temporal dynamics of urban NH3 concentrations in Münster, northwest Germany, the role of road traffic and agriculture as NH3 sources and about the importance of ammonia for secondary particle formation (SPF). The NH3 mixing ratio was rather high (mean: 17 ppb) compared to other urban areas and showed distinct diurnal maxima around 10 a.m. and during the night at 9 p.m. The main source for ammonia in Münster was agriculture, but road traffic also contributed through local emissions from vehicle catalysts. NH3 from surrounding agricultural areas accumulated in the nocturnal boundary layer and contributed to SPF in the city center. Modeled emissions of NH3 as estimated by the Handbook for Emission Factors in combination with traffic counts were in the same magnitude for NH3. The size-resolved chemical composition of inorganic ions in PM10 was dominated by NH4 + (8.66 µg m−3), followed by NO3 − (3.89 µg m−3), SO4 2− (1.58 µg m−3) and Cl− (1.33 µg m−3). Particles in the accumulation range (diameter: 0.1–1 µm) showed the highest inorganic ion concentrations. The ammonium neutralization index J (111%) indicated an excess of NH4 + leading to mostly alkaline PM. High ammonia emissions from surrounding agricultural areas combined with large amounts of NOx from road traffic play a crucial role for SPF in Münster.